The effects of non-insulin anti-diabetic medications on the diabetic microvascular complications: a systematic review and meta-analysis of randomized clinical trials - Song Wen; Yue Yuan; Yanyan Li; Chenglin Xu; Lijiao Chen; Yishu Ren; Congcong Wang; Yanju He; Xiucai Li; Min Gong; Xinlu Yuan; Dongxiang Xu; et al. (BMC Endocrine Disorders)
Abstract Introduction Although the onset and progression of diabetic microvascular complications are linked to glycemic control, various antihyperglycemic drugs with distinct treatment targets may positively impact microvascular lesions beyond their glucose-lowering effects. Therefore, this systematic review emphasizes the clinical therapeutic implications of non-insulin anti-diabetic medications for diabetic microvascular complications. Methods We retrieved published literature reporting randomized clinical trials (RCTs) on the effects of microvascular complications, including diabetic nephropathy (DN), diabetic peripheral neuropathy (DPN), and diabetic retinopathy (DR), from authenticated clinical databases: PubMed, Excerpta Medica database (EMBASE), and Web of Science. We synthesized data, including the continuous variable indices: estimated glomerular filtration rate (eGFR), urinary albumin to creatinine ratio (UACR), and urinary albumin excretion rate (UAE). Indices measuring cardiovascular autonomic neuropathy (CAN), vibration detection threshold (VDT), and retinal nerve fiber thickness (RNFL) were used to calculate microvascular effects. We also synthesized dichotomous variable indices, including the risks for DR and DPN. Results According to our analyses, there was sparse evidence strongly supporting that metformin (MET), Sulfonylurea (SUs), Repaglinide (Repa), or α-Glucosidase inhibitors (α-GIs) could benefit diabetic microvascular complications when adopted as monotherapy. Regardless of the no change in eGFR, two trials reporting Thiazolidinediones (TZDs) significantly reduced the UACR, while other clinical trials reported an increase in VDT and improvement in DR. Sodium glucose co-transporter inhibitors (SGLT-2i) and Glucagon-like peptide-1 receptor agonists (GLP-1RA) both showed protective effects in preventing eGFR decline, with only SGLT-2i demonstrating a significant reduction in UACR. A recent trial showed that Dipeptidyl Peptidase IV inhibitors (DPP-IVi) may potentially reduce the risk of DPN, while GLP-1RA did not prove to alter the measures of CAN and DPN. However, the SUSTAIN 6 trial revealed that Semaglutide may increase the risk of DR. Conclusion Besides their anti-hyperglycemic properties, some currently reviewed medications may exhibit unique anti-microvascular abilities. Due to ambiguous and conflicting available results, more emerging or ongoing trials will address this issue and could benefit clinical strategies for personalized treatment practices. Clinical trial number Not applicable.